Effects of an advanced driver training program on young traffic offenders' subsequent crash experience. (October 2020) - Wang, Yudan C.; Foss, Robert D.; O'Brien, Natalie P.; Goodwin, Arthur H.; Harrell, Stephanie
Highlights: The only experimental evaluation to date of an advanced driver training program. Quasi-experimental design with a relatively large sample. The hands-on program produced no more safety benefits than traditional ones. Abstract: Introduction: Advanced driver training programs (ADTPs) are a popular approach to improve young driver safety in the U.S. These programs provide behind-the-wheel experiences in controlled settings that are thought by parents, teens, and others to be highly valuable. However, none of these programs have been carefully evaluated. The purpose of the current study was to evaluate one such program. Methods: We randomly assigned 599 young drivers who had received a traffic citation to an ADTP, or a control condition involving traditional classroom traffic safety education. Results: Time-to-event (survival) analyses of participants' subsequent crash experience over the course of 550 days revealed no meaningful difference in the number of days to the first crash for those who participated in the experimental or control programs, or those who left the study. Conclusions: The advanced driver training program evaluated in this study produced no more crash reduction benefits for participants than traditional classroom-based programs. A strength of the study was the relatively large sample size and the random assignment of participants to conditions, which ruled out self-selection bias. However, this group, recruited as a result of traffic violation, may have already developed a higher risk driving demeanor than was the case in the broader population of young drivers. Additional research with other ADTPs and with a population of drivers who are earlier in their driving careers, using a similarly strong experimental design, is urgently needed to inform traffic safety practitioners and parents about the potential value of such hands-on programs.